Cuticular hydrocarbons as potential mediators of cryptic species divergence in a mutualistic ant association. Issue 16 (21st July 2019) - Hartke, Juliane; Sprenger, Philipp P.; Sahm, Jacqueline; Winterberg, Helena; Orivel, Jérôme; Baur, Hannes; Beuerle, Till; Schmitt, Thomas; Feldmeyer, Barbara; Menzel, Florian
Abstract: Upon advances in sequencing techniques, more and more morphologically identical organisms are identified as cryptic species. Often, mutualistic interactions are proposed as drivers of diversification. Species of the neotropical parabiotic ant association between Crematogaster levior and Camponotus femoratus are known for highly diverse cuticular hydrocarbon (CHC) profiles, which in insects serve as desiccation barrier but also as communication cues. In the present study, we investigated the association of the ants' CHC profiles with genotypes and morphological traits, and discovered cryptic species pairs in both genera. To assess putative niche differentiation between the cryptic species, we conducted an environmental association study that included various climate variables, canopy cover, and mutualistic plant species. Although mostly sympatric, the two Camponotus species seem to prefer different climate niches. However in the two Crematogaster species, we could not detect any differences in niche preference. The strong differentiation in the CHC profiles may thus suggest a possible role during speciation itself either by inducing assortative mating or by reinforcing sexual selection after the speciation event. We did not detect any further niche differences in the environmental parameters tested. Thus, it remains open how the cryptic species avoid competitive exclusion, with scope for further investigations. Abstract : The two mutualistically associated ant species Crematogaster levior and Camponotus femoratus from the neotropics both exhibit unusually high cuticular hydrocarbon (CHC) diversity. By analyzing genetic barcodes, cuticular hydrocarbon profile, and morphological data, we can conclusively show that this diversity in fact reflects cryptic species and argue that CHC diversification in this case might have played a role in species divergence.